Sintering Effect on the Microstructure And Magnetic Properties of Co-Alxoy Composite Compound - Sri Mulyaningsih; Setyo Purwanto; Mujamilah Mujamilah; Wisnu A. Adi; Azwar Manaf (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2008)
Research on sintering effect on the micro structure and the magnetic properties of composite Co-AlxOy materials has been done. The experiment was carried out by high energy milling (HEM) to refine Co and Al sample powder, followed by sintering process. The composition of sample was Co73Al27 wt% with weight ratio to the ball was 1:2.7. The milling time was varied within 4.5, 12 and 20 hours, while sintering process was conducted at 384ºC and 484ºC. Several new peaks were found after sintering process and identified as a Co-Al2O4 compound. The experiment data shows the saturation magnetization Ms value was decline for the entire sample by the sintering process. The Mr value for the 12h milling was remind stable about 9 emu/gr but, for 4.5 milling was decline from 17.5 to 9.2 and 6.2 emu/gr , while for 20h milling from 13,5 to 9.25 and 8 emu/gr. No visible changes in the microstructure are observed.